Morphology of juvenile stages of Kuschelina bergi (Harold) with biological information (Coleoptera, Chrysomelidae, Alticini) - Cabrera, Nora Clara (2016)
Kuschelina bergi (Harold, 1881) is being studied to be evaluated as a natural enemy of Phyla nodiflora var. minor (Hook.) N. O’Leary & Múlgura (Verbenaceae), an invasive weed in Australia. Eggs, and 1st and 3rd instar larvae are described and illustrated for the first time. The following characters distinguish Kuschelina bergi: presence of two medial setae in prosternum, mesosternum and metasternum, absence of tubercle on sternum I and eight setae in abdominal segment IX. The 3rd instar larvae of K. bergi resemble Kuschelina gibbitarsa (Say) larvae: the body shape and details of mouthparts are similar, but the morphology of the mandible is different, as is the tarsungulus which has a single seta. Differences between K. bergi and other known larvae of Oedionychina are discussed. New biological data based on laboratory rearing and field observation are also presented and discussed.